Clinical Efficacy of Gandakang Tablets plus Methylprednisolone in Patients with Systemic Lupus Erythematosus. (28th April 2022) - Wang, Min; Li, Guoquan; Wang, Shanzhi; Ye, Feng; Huang, Yanni; Wang, Huanan; Guo, Feng
Abstract : Objective . To evaluate the clinical efficacy of Gandakang tablets plus methylprednisolone in patients with systemic lupus erythematosus (SLE). Methods . From February 2015 to February 2019, 60 eligible patients with SLE were recruited and assigned via the random number table method at a ratio of 1 : 1 to receive either methylprednisolone (control group) or Gandakang tablets plus methylprednisolone (observation group). The primary endpoint was clinical efficacy, and the secondary endpoints included Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score, immunoglobulin (Ig), inflammatory factor levels, and adverse events. Results . Gandakang tablets plus methylprednisolone were associated with a significantly higher treatment efficacy versus methylprednisolone alone (P < 0.05 ). Gandakang tablets plus methylprednisolone resulted in significantly lower SLEDAI scores and lower levels of IgG, IgM, IgA, tumor necrosis factor- α (TNF- α ), interleukin-4 (IL-4), and interleukin-6 (IL-6) versus single medication of methylprednisolone (P < 0.05 ). The two groups showed a similar incidence of adverse events (P > 0.05 ). Patients given Gandakang tablets plus methylprednisolone had higher mental health, emotional role, physical role, social functioning, and bodily pain scores versus those receiving the monotherapy of methylprednisolone (P < 0.05 ). Conclusion . Gandakang tablets plus methylprednisolone is effective in the treatment of SLE by enhancing the patients' immunity, mitigating the inflammatory response, eliminating negative emotions, and improving their quality of life.